Clozapine re-trial in a patient with repeated life threatening pneumonias - Galappathie, Nuwan; Seth, Vikas; Begum, Amina (Acta Biomedica Atenei Parmensis, 2014)
Background and aim of the work: There has been an increasing amount of evidence to suggest a link between Clozapine and pneumonia. Whilst an exact mechanism for disease causation has not been identified excess salivation, impaired swallowing and abnormalities within the immune system have all been implicated. Within forensic services there is often a need to treat complex patients with Clozapine, even when a past history of pneumonia is present. Methods: We present a case report on a forensic inpatient who has suffered repeated episodes of Clozapine associated pneumonia and highlight methods for good practice. Results: Where appropriate, Clozapine can still be used in complex patients who have suffered previous pneumonias and have additional risk factors for chest infections, provided that robust risk reduction, infection surveillance and treatment interventions are employed. Conclusions: Practical measures can be employed to enable safe treatment of forensic patients with Clozapine, this includes risk factors for chest infections being carefully controlled such as asthma, Chronic Obstructive Airways Disease or diabetes. Patients should be carefully monitored for signs of infection by way of regular physical examinations and appropriate tests when required. Should signs of pneumonia arise the dose of Clozapine may need to be reduced and the infection aggressively treated with antibiotic medication.